Unsung Women `S Freedom Fighters of Tamil Nadu 1752-1947 - T. Balasubramanian; V.Venkatraman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
India’s Freedom Struggle cannot be completed without mentioning the participation of women in all struggles and their sacrifices. Many of us don’t know that women of India fought the British along with the men folk. Women have to sacrifice the family, and many household roles to participate in the freedom struggle. We have to recognize the role and sacrifice made by the women of India. The are the symbol and the driving force for many who wish to fight for equality and injustice. The history of Indian National Movement definitely would be incomplete without mentioning the sacrifice of Indian Women. The sacrifice rendered by the Women folk of India will occupy the significant place. They really fought with true spirit and unafraid courage and faced a numerous tortures hardship and exploitations to learn us freedom. When most of the men freedom fighters were in prison the women folk came forward and took charge of the national struggle. The article entitled, “Capsule of Biographies of Unsung Heroines” deals with historical sources of some of the women freedom fighters of Tamilnadu.